Contribution of Parenting Styles on Girl Child Secondary School Completion in Abim Secondary School in Abim District - Ogwang Okuda John (Uganda Christian University, 2024)
This research investigated the contribution of various parenting styles on the completion of secondary education by girls in Abim Secondary School, Abim District. Understanding the influence of parenting on educational outcomes is crucial, particularly in contexts where female education faces significant challenges. The study focused on four primary parenting styles: authoritative, authoritarian, permissive, and neglectful, examining their impact on factors such as academic performance, school attendance, motivation, and psychological well-being among female students. Utilizing a mixed-methods approach, the research combined quantitative surveys with qualitative interviews involving students, parents, and educators to gain a comprehensive understanding of how parenting practices affect girl child secondary school completion. The study finds that authoritative parenting, which balances discipline with emotional support, is most conducive to academic success and higher completion rates. In contrast, authoritarian and neglectful parenting styles are associated with increased dropout rates, largely due to the negative effects on students' self-esteem and motivation. Permissive parenting also poses challenges, as a lack of structure and guidance can lead to poor academic discipline and performance. The findings underscore the importance of promoting positive parenting practices through community-based education programs that emphasize the role of parental involvement and support in ensuring girls' educational success. Additionally, the study advocates for stronger partnerships between schools, parents, and community organizations to provide the necessary resources and support systems that can help girls overcome challenges associated with less effective parenting styles. By addressing these issues, the research aims to contribute to strategies that improve girl child secondary school completion rates in Abim District, thereby enhancing opportunities for gender equality and empowerment in the region